2021
DOI: 10.1111/1467-9817.12343
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of reading and spelling skills in German: the role of morphological awareness

Abstract: Background: The role of morphological awareness for literacy development is noncontroversial, but it is likely to depend on the characteristics of a specific orthography. Previous studies analysing the role of morphological awareness are mainly based on English samples; thus, it is unclear how generalisable these results are. In the current study, we evaluated the predictive pattern of morphological awareness on reading and spelling in German, which is characterised by high consistency between morphology and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 63 publications
4
23
2
2
Order By: Relevance
“…In spelling, phoneme-grapheme is less consistent, and instead, morphemes provide consistency. In line with this asymmetry, Görgen et al (2021) found that morphological awareness was a particularly strong predictor of spelling ability. Using novel internet-based techniques for data collection enabled the authors to reach a large sample of 3,122 children (9 to 10 years old).…”
Section: Cross-language Considerationsmentioning
confidence: 64%
See 3 more Smart Citations
“…In spelling, phoneme-grapheme is less consistent, and instead, morphemes provide consistency. In line with this asymmetry, Görgen et al (2021) found that morphological awareness was a particularly strong predictor of spelling ability. Using novel internet-based techniques for data collection enabled the authors to reach a large sample of 3,122 children (9 to 10 years old).…”
Section: Cross-language Considerationsmentioning
confidence: 64%
“…One of the goals of this special issue was to bring together empirical evidence from different languages and contexts to inform these questions. To this end, this special issue includes studies in Chinese (Cantonese; Qiao et al, 2021), French (Rassel et al, 2021), German (Fleischhauer et al, 2021;Görgen, De Simone, Schulte-Körne, & Moll, 2021) and Norwegian (Lyster et al, 2021) and studies in English that draw upon the varied educational contexts of the United Kingdom (Dawson et al, 2021;James et al, 2021), the United States (Goodwin et al, 2021) and Canada (Georgiou et al, 2021;Ginestet et al, 2021). Qiao et al (2021) explored the relationship between morphological awareness and reading comprehension in both Chinese and English with Chinese-English bilingual children in Hong Kong (8 to 10 years old).…”
Section: Cross-language Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dagegen ist bei Rechtschreibfehlern, die eine fehlende Einsicht in die Systematik der deutschen Orthografie erkennen lassen (siehe 2c), anzunehmen, dass diese über die Förderung der morphematischen Bewusstheit überwunden werden können (vgl. Galuschka et al, 2020;Görgen, De Simone, Schulte-Körne & Moll, 2021;Volkmer, Schulte-Körne & Galuschka, 2019;Kirby et al, 2012). Dieser Zusammenhang ist damit zu begründen, dass die Morphologie im Gegensatz zu phonologisch und / oder morphosyntaktisch geprägten Bereichen (Phonem-und Deklinationssystem) der Rechtschreibnorm im größeren Maße unabhängig vom frü-hen Spracherwerb durch sprachanalytische und schriftsystematische Operationen erlernt werden kann (siehe Abbildung 1).…”
Section: Annahmen Und Modellierungskriterienunclassified